2006
DOI: 10.1103/physreve.73.036612
|View full text |Cite
|
Sign up to set email alerts
|

Method to determine cutoff frequencies for acoustic waves propagating in nonisothermal media

Abstract: A method to determine cutoff frequencies for linear acoustic waves propagating in nonisothermal media is introduced. The developed method is based on wave variable transformations that lead to Klein-Gordon equations, and the oscillation theorem is applied to obtain the turning point frequencies. Physical arguments are used to justify the choice of the largest turning point frequency as the cutoff frequency. The method is used to derive the cutoff frequencies in nonisothermal media modeled by exponential and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 19 publications
1
57
0
1
Order By: Relevance
“…The analytical solutions obtained by these authors showed that linear Alfvén waves form standing wave patterns in their isothermal model. The reason for the existence of these standing waves is wave reflection and the resulting constructive interference between the propagating and reflected Alfvén waves (see also Musielak et al 2006).…”
Section: Discussion Of the Analytical And Numerical Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The analytical solutions obtained by these authors showed that linear Alfvén waves form standing wave patterns in their isothermal model. The reason for the existence of these standing waves is wave reflection and the resulting constructive interference between the propagating and reflected Alfvén waves (see also Musielak et al 2006).…”
Section: Discussion Of the Analytical And Numerical Resultsmentioning
confidence: 99%
“…(18) and (19) in their standard form, i.e., without the first derivative term; the wave equations written in their standard forms are often referred to as Klein-Gordon equations (e.g., Rae & Roberts 1982;Musielak et al 1987Musielak et al , 2006. Because there is no term with the first derivative in the wave equation for V z , this equation is already written in its standard form.…”
Section: Cutoff-frequency With Approximate Wave Travel Timementioning
confidence: 99%
See 3 more Smart Citations